Credit rationing: A growth obstacle to informal SMEs in the Western Cape City Bowl of Cape Town - Magangxa, Fadzai (Graduate School of Business (GSB), 2023)
The study investigated the limit of credit by financial institutions which is an obstacle on the growth of informal survivalist and non-survivalist small enterprises which operate in the Western Cape, Cape Town City bowl area. The objectives of the study were to examine the impact that credit rationing has on the growth of informal survivalist and non-survivalist Small Medium Enterprises (SMEs). The research employed a simple random probability technique to sample fifty (50) informal survivalist and non-survivalist SMEs owners or managers operating in Western Cape, Cape Town City centre area. The regression model to examine relationship between credit rationing and SME growth was estimated using the ordinary least estimation technique. The study results indicated that those enterprises that were granted a loan credit facility experienced growth in comparison to those firms who were not granted such facility. The experience of credit rationing was therefore reported to have a significant positive impact on the growth of informal survivalist and non-survivalist SMEs. The study recommends tax incentives benefits, financial institutions to support structure mechanism for informal SMEs through enabling tailor-made projects which entitles designing small amount lending financing packages at a lower return rate and less requirements for such enterprises. Additionally, the individual entrepreneurs have to focus on peer to peer lending, crowdfunding, borrowing from family members as alternative forms of borrowing from another without the mediation of financial institution and as a social network tool mechanism for also exchanging business growth information.